Regional variations in rural livelihoods: Challenges and opportunities - Belton, Ben; Filipski, Mateusz J.; Lambrecht, Isabel B.; Fang, Peixun (International Food Policy Research Institute, 2024)
Rural livelihoods in Myanmar are embedded in regional contexts that vary widely in terms of physical geography, climate and agroecology, local resource base, agrarian structure, infrastructure provision, proximity to urban areas and neighboring countries, social networks, institutions, and ethnicities. The composition of livelihoods in each administrative and geographic zone of the country reflects these diverse contexts. Marked variations in livelihood patterns are evident at multiple scales, from the zone or region down to township and village level, so that the composition of livelihoods in villages close to one another sometimes varies widely.